“Pseudomonas aeruginosa characterization and analysis based on its antimicrobial resistant pattern collected from hospital wastewater and adjacent community water.” - Sarah, Humaira Reza Khan; Faiza, Refat Rahman (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.